2020
DOI: 10.1002/bdr2.1827
|View full text |Cite
|
Sign up to set email alerts
|

Folate intake, markers of folate status and oral clefts: An updated set of systematic reviews and meta‐analyses

Abstract: Background There has been a longstanding debate about the role of folate in the etiology of orofacial clefts (OFCs). Studies of different measures of nutritional intake or folate status have been done to investigate the possible role of folate in the prevention of OFC. Only one knowledge synthesis has attempted to bring together different types of evidence. The aim of the present work was to update it. Methods Evidence for associations between OFC and dietary folate, supplement use, folic acid fortification, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
25
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(32 citation statements)
references
References 75 publications
(121 reference statements)
4
25
0
3
Order By: Relevance
“…Maternal folic acid supplementation (FAS) before and during early pregnancy is a well-established prevention approach for neural tube defects (NTDs). As facial mesenchyme is derived from neural crest, the protective effect of maternal FAS on oral clefts has been studied in various populations, but the findings are inconclusive 5 8 . Most observational studies conducted in Europe 9 14 , America 15 17 , and Asia 18 21 , have shown that maternal FAS during early pregnancy is associated with decreased risk of nonsyndromic CL/P (NsCL/P), while other investigations in these areas did not 22 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Maternal folic acid supplementation (FAS) before and during early pregnancy is a well-established prevention approach for neural tube defects (NTDs). As facial mesenchyme is derived from neural crest, the protective effect of maternal FAS on oral clefts has been studied in various populations, but the findings are inconclusive 5 8 . Most observational studies conducted in Europe 9 14 , America 15 17 , and Asia 18 21 , have shown that maternal FAS during early pregnancy is associated with decreased risk of nonsyndromic CL/P (NsCL/P), while other investigations in these areas did not 22 27 .…”
Section: Introductionmentioning
confidence: 99%
“…Another review has reported that mandatory folic acid fortification of wheat and/or maize flour may have beneficial effects on non-syndromic CL/P [26]. A recent meta-analysis also has shown that the risk of non-syndromic orofacial clefts was reduced among pregnant women with folic acid-containing supplements during the etiologically relevant period [27]. In Zhongshan of China, every pregnant woman is recommended daily intake of 0.4 mg folic acid in 3 months before pregnancy and in first 3 moths of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Concerning environmental risk factors, previous researches, which have shown consistency, have proposed smoking consumption during pregnancy and gestational diabetes as maternal risk factors [ 4 , 9 , 10 ]. Other associations have been reported with less consistency, namely alcohol consumption during pregnancy, intrapartium interval, maternal and paternal age, and nutritional deficiencies (folic acid, vitamin A and B12, and zinc) [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Furthermore, both extremes of maternal body mass index (BMI) have been associated with birth defects, but with controversial results in the literature [ 10 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%